Hubungan Status Gizi dengan Karies pada Gigi Molar Pertama Bawah Permanen pada Anak Usia 6-8 Tahun di SDN 36 Manado - Aulia, Avita; Gunawan, Paulina N.; Kawengian, Shirley E. S. (e-GiGi, 2019)
Abstract: Caries is the presence of a cavity on the tooth caused by the activity of microorganism on fermented carbohydrate. Nutritional status is resulting from food consumption, which is one of the factors that influence the occurence of dental caries. This study was aimed to obtain the relationship between nutritional status and caries in permanent lower first molar among students of SDN 36 (elementary school) Manado. This was an analytical study using a cross sectional design. There were 48 students at SDN 36 Manado aged 6-8 years in this study obtained by using total sampling technique. We used the nutritional status based on length-for-age and BMI-for-age using the z-scores WHO anthropometrical standards for children aged 5-18 years and examined the oral cavity whether there was caries in permanent lower first molars. The results showed that caries in permanent lower first molars was found in 77.1% of subjects. Nutritional status based on length-for-age showed normal category (83.3%) and short stature/stunted (16.7%). The nutritional status based on BMI-for-age showed obese category (22.9%), overweight (8.3%), normal (60.5%), wasted (8.3%), and severely wasted (0.0%). The Fisher’s Exact test and the Chi-Square test showed that the relationship between length-for-age and the occurence of caries had a p-value of 1,000 meanwhile the relationship between nutritional status based on BMI-for-age and the occurence of caries had a p-value of 0.024. Conclusion: There was a significant relationship between nutritional status based on BMI-for-age and caries in the permanent lower first molars in children aged 6-8 years at SDN 36 Manado.Keywords: dental caries, permanent lower first molar, nutritional status Abstrak: Karies adalah adanya rongga pada yang disebabkan oleh aktivitas jasad renik terhadap karbohidrat yang dapat diragikan. Status gizi merupakan keadaan tubuh sebagai akibat konsumsi makanan, yang menjadi salah satu faktor yang dapat memengaruhi proses terjadinya karies gigi. Penelitian ini bertujuan untuk mengetahui hubungan antara status gizi dengan karies gigi molar pertama bawah permanen pada anak usia 6-8 tahun di SDN 36 Manado. Jenis penelitian ialah analitik dengan desain potong lintang. Pengambilan sampel menggunakan teknik total sampling terhadap seluruh siswa di SDN 36 Manado berusia 6-8 tahun pada tahun 2019 yang berjumlah 48 orang. Pada penelitian ini dilakukan pengukuran status gizi TB/U dan IMT/U berdasarkan SD dengan standar baku antropometri WHO untuk anak usia 5-18 tahun serta pemeriksaan rongga mulut untuk melihat ada tidaknya karies pada gigi molar pertama bawah permanen. Hasil pemeriksaan menunjukkan terdapatnya karies pada gigi molar pertama bawah permanen sebesar 77,1% subyek. Status gizi berdasarkan TB/U didapatkan subyek kategori normal (83,3%) dan pendek/stunted (16,7%). Status gizi berdasarkan IMT/U didapatkan kategori obesitas (22,9%), gemuk (8,3%), normal (60,5%), kurus (8,3%), serta sangat kurus (0,0%). Hasil uji Fisher’s Exact dan uji Chi-Square menunjukkan untuk TB/U nilai p=1,000 sedangkan untuk IMT/U nilai p=0,024. Simpulan: Terdapat hubungan bermakna antara status gizi berdasarkan IMT/U dengan karies gigi molar pertama bawah permanen pada anak usia 6-8 tahun di SDN 36 Manado.Kata kunci: karies gigi, molar pertama bawah permanen, status gizi